Resistência ao cisalhamento de um solo tropical não saturado considerando altas sucções - Kuhn, Vinícius de Oliveira (2014)
Often overlooked, the mechanical behavior of unsaturated soils when subjected to high suctions is relevant for several engineering problems. These range from common questions regarding the behavior of near-surface desiccated clays to very specific challenges, such as the design of nuclear waste disposal barriers. In this context, the objectives of this work are to experimentally study the shear strength of a compacted unsaturated tropical soil considering high suctions, to evaluate the performance of existing shear strength models, and to develop a model that addresses the particular behavior observed under high suctions. The material studied, a residual clayey soil from Goiania, GO, Brazil derived from mica schist, was semi-statically compacted at optimum conditions corresponding to the Standard Proctor. An extensive experimental program was undertaken, manly comprised of CDnsat triaxial tests for relatively low matric suctions (i.e., lower than 300 kPa), CW triaxial tests for relatively high total suctions, and Brazilian tensile tests also for high total suctions. The CW triaxial and tensile tests required the measurements of suction before and after failure. These measurements were carried out using both the filter paper technique for total and matric suction and a dew point potentiometer for total suction. In addition, tests were performed to determine the soil-water characteristic curve (SWCC) at unconfined condition. Data obtained from unsaturated triaxial tests also allowed the measurement of the SWCC, specifically for the soil consolidated at different confining stresses and for the soil subjected to deviator stresses. The experimental program was complemented by consolidated-drained triaxial tests and isotropic compression tests, both under saturated conditions. The monitoring of several stress, strain, and volume-mass state variables allowed for a detailed evaluation of soil behavior. Based on the results of the experimental program, it was determined that for total suctions ranging from zero up to approximately 10,000 kPa there is significant nonlinear shear strength increase. Beyond that suction, shear strength decreases as the soil desaturates. The shear strength loss depends on the net normal stress, with the soil presenting smaller reductions in shear strength for higher confining stresses. A remarkable relationship between the SWCC and the shear strength was observed, with the point of maximum strength corresponding to the air-entry value of the micropores. The relationship between shear strength and the water stored in micropores that are generally present within clay aggregates indicates the importance of the mechanical stability of these soil aggregates. The performance of different fitting and prediction models was evaluated considering both low suctions and the wide range of suctions used in the experimental program. Existing prediction models based on SWCC proved inaccurate for high suctions, requiring changes in their formulations. A new family of models that consider the entire range of suctions, including the loss of shear strength, was proposed. Finally, the prediction models using the SWCC of the soil under deviator stress (i.e., peak conditions) was evaluated, showing that the use of the unconfined SWCC presents superior prediction results to both low suctions and the wide range of suctions.